Penyuluhan Pencegahan Pernikahan Dini Pada Pemuda Karang Taruna Desa Baletbaru Sukowono Jember Sebagai Upaya Prefentif Resiko Stunting Pada Anak - Yussuli Yussuli; Saini Saini; Fajar Ainul Yaqin (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
Early marriage is one of the issues that contributes to the high rate of stunting in children in Indonesia, especially in rural areas. In Baletbaru Village, Sukowono, Jember, early marriage is still a common phenomenon, so preventive measures are needed to reduce the risk of stunting through education and counselling. The purpose of this assistance is to increase public knowledge and awareness, especially among adolescents, regarding the negative impacts of early marriage and the importance of nutrition in preventing stunting. The method used is Participatory Rural Appraisal (PRA), which directly involves the community in every stage of assistance, from identifying problems to formulating solutions. The results of the assistance showed a significant increase in participants' understanding of the negative impacts of early marriage, with 85% of participants feeling they understood the issue better. In addition, 90% of participants were committed to sharing information with their environment. The implications of this assistance indicate that ongoing counselling is urgently needed, and further collaboration with the government and health institutions is recommended to expand the reach of education and intensive assistance for at-risk communities.